2019
DOI: 10.1111/birt.12459
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use and quality of Internet discussion forums in pregnancy: A qualitative analysis

Abstract: Background The Internet is widely used as a source of health information to assist decision making in pregnancy. Concerningly, the quality of information shared on online pregnancy forums is unclear. Our objectives were to explore online pregnancy forum health‐related use and evaluate quality of information shared. Methods This retrospective qualitative study had two phases of data collection and analysis. First, thematic analysis of a representative sample (n = 480) of posts explored motivators for forum use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…Therefore, the first site was retained, with the remainder deemed insufficient for sampling. This approach is comparable with previous research that used discussion forums [ 19 , 20 ].…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, the first site was retained, with the remainder deemed insufficient for sampling. This approach is comparable with previous research that used discussion forums [ 19 , 20 ].…”
Section: Methodssupporting
confidence: 86%
“…Posts were collected sequentially, as they appeared on the day of sampling, and if a post met the exclusion criteria, the following post was selected until 20 posts were obtained. Posts were extracted in a deidentified format into an Excel (Microsoft) document that included the post title, date, and content, comparable with previous research [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Online support groups have previously been shown to be commonly accessed by women during this period. They provide an accessible, peer-to-peer opportunity for information sharing, individualized information seeking, and social and emotional support from women in a comparable life stage [ 21 , 22 ]. Accessibility and anonymity provided by online forums facilitates a disinhibited expression of feelings without concern of consequences or conflict from close connections.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially concerning, given that as many as 70-75% of pregnant women do not speak to their health care providers about information retrieved from the Internet [23,30,34]. Furthermore, one recent study analyzing the quality of online information in Internet discussion forums in pregnancy found that 24.3% of responses lacked credible evidence and 5.5% were potentially harmful [38]. Yet women typically perceive online pregnancy information to be reliable and of high quality [1,3,5,9,30,34], and use it to inform their health care decisionmaking [4,5,12,14].…”
Section: Discussionmentioning
confidence: 99%